The Influence of Base Isolator on The Reinforced Concrete Structures at Sapadia Mataram Hotel Earthquake-Induced - Zarkasi, Ahmad; Hariyadi, Hariyadi; Hidayati, Nurul; Fitrayudha, Adryan; Heru, M. (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2024)
Ring of Fire and at the intersection of three tectonic plates. Efforts are needed to minimize earthquake damage, one of which is the use of a base isolator system. This study aims to determine the effect of using High Damping Rubber Bearing (HDRB) with a diameter of 800 mm on the behavior of reinforced concrete structures in tall buildings under seismic loads. The research location is the 7-story Sapadia Hotel building in the city of Mataram. The research is conducted by analyzing a 3D model of the fixed base structure and the base isolator structure using numerical analysis. The results show an increase in the base displacement of the base isolator structure by 59% in the x-direction and 44% in the y-direction, while the inter-story displacement decreases by 36% in the x-direction and 69% in the y-direction. The use of base isolators can reduce the shear force by 35% in the x-direction and 15% in the y-direction. Based on the pushover analysis, the roof displacement values for the fixed base and base isolator structures are 0.159 m and 0.129 m respectively. These values can be used to determine the structural performance level according to ATC-40. The maximum drift value for the fixed base structure is 0.0055 m. For the base isolator structure, the maximum drift value is 0.0044 m, categorized as Immediate Occupancy (IO). This value can be used to determine the performance level of the structure based on ATC-40. The maximum drift value of the fixed base structure is 0.0055m. While in the base isolator structure, the maximum drift value is 0.0044 m which is included in Immediate Occupancy (IO). Thus, the use of base isolators in high-level buildings is able to reduce post-earthquake damage and the building is still safe to continue using.